Assessment of nutrient and heavy metal contents in a sewage sludge treatment plant through hydrothermal carbonization - Tahmid Sadique Mazumder; Rifat Mahmud; Md Mominur Rahman; Md Shahinoor Islam (South African Journal of Chemical Engineering, 2025)
This study investigates the fertilizer potential of sewage sludge from a sewage treatment plant through hydrothermal carbonization (HTC) by assessing the nutrient and heavy metal contents. HTC was conducted at 190 °C, 210 °C and 230 °C at a constant retention time of 10 min maintaining a solid-to-water ratio (1:9), converting the dried sewage sludge (DSS) from the sedimentation basin into hydrochar and a nutrient-rich liquid phase. The organic nitrogen declined in the solids from 1.75 % to 0.89–1.46 % through HTC, whereas the ammonium-N increased (300–800 mg/kg). In the HTC liquor, 325–525 ppm organic nitrogen and 320–760 ppm ammonium-N were found. Hydrochars exhibited significant total phosphorus ranging from 1.95 % to 2.35 % and higher C:N ratio reaching 13.45 for 230 °C treatment indicating slow-nitrogen release property. Among other nutrients, 1.23–1.38 % calcium (Ca), 0.22–0.25 % sodium (Na) and 0.19–0.21 % potassium (K) were found in the hydrochar. On the other hand, 52.2–561.7 ppm phosphates, 210.4–498.5 ppm Ca, 48.19–51.35 ppm K and 28.63–84.40 ppm Na were incorporated within the HTC liquor. Among the heavy metals, the concentrations of arsenic (As), copper (Cu), zinc (Zn), nickel (Ni), cadmium (Cd), lead (Pb) and chromium (Cr) were assessed. Four (Cu, Zn, Ni and As) of the eight metals were found to be above the toxicity limit. However, in the liquor, the concentrations of heavy metals were negligible (<2 ppm). Therefore, the study indicates that the use of sewage sludge has a potential to be used as nutrients for cultivating crops which will reduce the import of chemical fertilizer and enhance the utilization of sewage sludge sustainably.